Analysis Of Strategy For Developing HR Competencies In Facing The Era Of Digitalization At The Secretariat Of South Lampung Regional House Of Representatives - Prasetya, Bayu; Dunan, Hendri (Cita konsultindo, 2026)
The development of human resource (HR) competencies is a key factor in supporting digital transformation within government institutions, including the Secretariat of the Regional House of Representatives (DPRD) of South Lampung Regency. This study aims to analyze strategies for developing HR competencies in facing the era of digitalization and to identify supporting and inhibiting factors. The research uses a qualitative approach with participatory observation methods supported by interviews and documentation studies. Data analysis is conducted using the Miles and Huberman model and reinforced with SWOT analysis. The results indicate that HR competency development is not yet optimal due to limited resources, low digital literacy, resistance to change, and infrastructure constraints. The strategies developed emphasize strengthening the digital competencies of staff, improving institutional frameworks, and enhancing technological support and an adaptive work culture.